EFL STUDENTS’ OBSTACLES TO SPEAKING ENGLISH; WHAT AND WHY - Fifi Astuti (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
ABSTRACT: This research is carried out to answer the question: (1) what are the speaking problems encounter by third semester students of English Department University of Islam Malang? (2) what are the factors that cause students difficulties in speaking English? .This research is used quantitative and descriptive qualitative approach. The subject of this research is third semester students at University of Islam Malang. To collect the data, the instruments used are a questionnaire and interview. The questionnaire responded by 73 students was used to get data about students’ problems in speaking English which covered five components of speaking skill such as grammar, vocabulary, pronunciation, fluency, and comprehension. Meanwhile, the interview involving two students’ interview was conducted to obtain deeper and detailed data about students’ problems and factors causing the problems.The result of this study, that the speaking problems faced by the English students from the third semester in the English department at the University of Islam Malang are similar. The speaking problems based the questionnaire is the external problems with the means score were 28.16 and the average score were 3.11. And the external problems is had by the item 13 with the mean score 3.47.The problems faced by the students based on the questionnaire are limited of vocabulary, difficult to give their idea, and difficult to responding the conversation. When the interviewed session, the result are mainly found in grammar, vocabulary, pronunciation, and fluency. In line with this, there are some factors that cause their difficulties in learning speaking English are performance conditions, affective factors, and topical knowledge.Regarding the time and subject limitation in the present study, the next research is suggested to reexamined students’ problems in speaking and factors that cause students difficulties in speaking English by use more than two instruments and used more subjects to interview and to interview many times to achieve data saturation. So that the data are more valid. keywords: Speaking, Speaking Problems, Descriptive